QSTEM kit: The Secrets of the Ocean in Al Quran - Ab Hamid, Hafiza; Mohamed Khalid, Muhammad Nazir; Khalid, Mohd Firdaus; Abd Rahim, Mohd Azrin; Azman, Nurshahirah; Abd Mutalib, Ai’syah; Mohd Fithri, Muhammad Hazim Najwan; Jamnul Azmin, Fudhla Asma’; Badrulazlan, Muhammad Mirza; Azman, Hazeeq Hazwan (Multidisciplinary Applied Research and Innovation, 2021)
There are many places in Al Quran that integrates the knowledge of science. Thus, it has been used as references for many researches nowadays. As the interest of learning science in Al Quran arises, it is essential to develop a STEM kit teaching tool in touting science and Al Quran to younger generations. This product is known as QSTEM kit: The secrets of the ocean in Al Quran, focusing on the verse specified in Al Quran on ocean. The activities in this kit includes floating eggs, invisible ink and salt density. These interactive activities instill the fun-learning approach in understanding the concept of density. This product will help the teachers to teach their students about the relationship between science and Al Quran especially about salt in the ocean and the concept of density. A preliminary survey was conducted and positive feedback has been observed from teachers and students on this kit. Further development is required to improve the kit for commercialization. There is a demand for an Islamic integrated stem kit in order to prepare a resilient future generation that will be well-equipped, both academically and spiritually.